2011
DOI: 10.1176/appi.ajp.2011.10101436
|View full text |Cite
|
Sign up to set email alerts
|

Gabapentin Combined With Naltrexone for the Treatment of Alcohol Dependence

Abstract: Objective Naltrexone, an efficacious medication for alcohol dependence, does not work for everyone. Symptoms (e.g. insomnia, mood instability), most evident during early abstinence, might respond better to a different pharmacotherapy. Gabapentin may reduce these symptoms and early relapse. This clinical trial evaluated whether gabapentin, in conjunction with naltrexone, was better than naltrexone alone and/or placebo during the early drinking cessation phase (first six weeks) and whether this effect persisted.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
114
0
3

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 133 publications
(117 citation statements)
references
References 34 publications
0
114
0
3
Order By: Relevance
“…Participants completed the RHDQ during a baseline visit before medication randomization. Study 1 evaluated the effects of naltrexone alone and in combination with gabapentin (Anton et al, 2011). Study 2 evaluated the effects of naltrexone alone and in combination with aripiprazole.…”
Section: Participantsmentioning
confidence: 99%
“…Participants completed the RHDQ during a baseline visit before medication randomization. Study 1 evaluated the effects of naltrexone alone and in combination with gabapentin (Anton et al, 2011). Study 2 evaluated the effects of naltrexone alone and in combination with aripiprazole.…”
Section: Participantsmentioning
confidence: 99%
“…However, the specificity of this effect is preliminary and needs further exploration as to validity and mechanism of action. Finally, a recent trial reported that the combination of gabapentin (up to 1200 mg/day) to naltrexone resulted in significantly improved drinking outcomes over naltrexone alone, and history of alcohol withdrawal was associated with better response in the naltrexonegabapentin group (Anton et al, 2011).…”
Section: Gabapentinmentioning
confidence: 99%
“…Behavioral symptoms of alcohol withdrawal, particularly in early abstinence, include impulsivity, anxiety, irritability, dysphoria, insomnia, and impaired concentration [92]. These symptoms overlap with the emotional and cognitive dysfunction resulting from TBI as described above [93].…”
Section: Behavioralmentioning
confidence: 99%